Global incidence and prevalence of pressure injuries in public hospitals: A systematic review - Al Mutairi, K.; Hendrie, Delia (2018)
© 2018 Elsevier GmbH Objectives: To summarize prevalence and incidence of pressure injuries (PIs) in public hospitals on a global scale to guide the development of PI prevention, strategies and planning for efficient use health resources. Design: A systematic literature review was conducted to examine the worldwide relevant literature published between 2000 and 2017 on the prevalence and incidence of PIs in hospitalised adult population. Data sources: A systematic search of databases (MEDLINE (Ovid), EMBASE (Ovid), CINAHL (EBSCO), and EconLit (EBSCO) was undertaken for English language articles published between 1st January 2000 to 31st March 2017. A systematic literature search was performed using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). Study selection: Peer-reviewed observational studies with reported data on the prevalence and incidence of PIs. The research articles selected for systematic review were assessed by two independent reviewers to check the methodological validity, using the Joanna Briggs Institute (JBI) Critical Appraisal Tools ‘Checklist for Prevalence Studies’. Results: The final selection for prevalence and incidence of PIs had 39 studies. Most of the studies reported the point prevalence (n = 26, 66.7%), whereas period prevalence was reported in 20.5% of the studies (n = 8), and the incident rate was reported in 5 studies (12.8%). The majority (n = 32, 82.0%) of the studies used the skin assessment method to collect the data, reviews of the medical records and administrative data were used in 3 studies each (7.7%). The overall global prevalence of PIs using point prevalence and period prevalence was 14.8% and 11.6%, respectively. The overall mean incidence of PIs was 6.3%. Conclusions: A careful and systematic review of all the retrieved citations yielded a rich source of evidence. In this systematic review of the literature, most of the studies employed the skin assessment technique to collate their data.